Changes in leaf functional traits with leaf age: when do leaves decrease their photosynthetic capacity in Amazonian trees?. (28th April 2021) - Menezes, Juliane; Garcia, Sabrina; Grandis, Adriana; Nascimento, Henrique; Domingues, Tomas F; Guedes, Alacimar V; Aleixo, Izabela; Camargo, Plínio; Campos, Jéssica; Damasceno, Amanda; Dias-Silva, Renann; Fleischer, Katrin; et al.
Abstract: Most leaf functional trait studies in the Amazon basin do not consider ontogenetic variations (leaf age), which may influence ecosystem productivity throughout the year. When leaf age is taken into account, it is generally considered discontinuous, and leaves are classified into age categories based on qualitative observations. Here, we quantified age-dependent changes in leaf functional traits such as the maximum carboxylation rate of ribulose-1, 5-biphosphate carboxylase/oxygenase (Rubisco) ( V cmax ), stomatal control ( Cgs %), leaf dry mass per area and leaf macronutrient concentrations for nine naturally growing Amazon tropical trees with variable phenological strategies. Leaf ages were assessed by monthly censuses of branch-level leaf demography; we also performed leaf trait measurements accounting for leaf chronological age based on days elapsed since the first inclusion in the leaf demography, not predetermined age classes. At the tree community scale, a nonlinear relationship between V cmax and leaf age existed: young, developing leaves showed the lowest mean photosynthetic capacity, increasing to a maximum at 45 days and then decreasing gradually with age in both continuous and categorical age group analyses. Maturation times among species and phenological habits differed substantially, from 8 ± 30 to 238 ± 30 days, and the rate of decline of V cmax varied from −0.003 to −0.065 μmol CO2 m −2 s −1 day −1 . Stomatal control increased significantly in young leaves but remained constant after peaking. Mass-based phosphorus and potassium concentrations displayed negative relationships with leaf age, whereas nitrogen did not vary temporally. Differences in life strategies, leaf nutrient concentrations and phenological types, not the leaf age effect alone, may thus be important factors for understanding observed photosynthesis seasonality in Amazonian forests. Furthermore, assigning leaf age categories in diverse tree communities may not be the recommended method for studying carbon uptake seasonality in the Amazon, since the relationship between V cmax and leaf age could not be confirmed for all trees.